Evaluation IP Neu - Andreas Haller; Stefan Staubli; Josef Zweimüller (Verlag des ÖGB GmbH, 2019)
Mit "IP Neu" wurden 2014 Neuregelungen im Bereich der Invaliditätspension (IP) umgesetzt. Zielsetzung ist die verstärkte Arbeitsmarktintegration von gesundheitlich beeinträchtigten Menschen. Dazu wurde die befristete Invaliditäts- bzw. Berufsunfähigkeitspension abgeschafft und stattdessen Umschulungs- oder Rehabilitationsgeld gewährt. Gleichzeitig werden Maßnahmen der beruflichen und medizinischen Rehabilitation durchgeführt. IP Neu reduzierte die IP Zuerkennungen um 40 Prozentpunkten zugunsten eines gleich hohen Anstiegs im Bezug von Rehabilitationsgeld. In den sonstigen arbeitsmarktrelevanten Zuständen zeigen sich kaum Unterschiede. Zwar zeigt sich eine leichte Verbesserung der Beschäftigungssituation, aber der Effekt ist quantitativ gering. Mögliche Gründe für die geringen Arbeitsmarkteffekte sind, dass AntragsstellerInnen sich noch in Rehabilitation befinden oder dass IP Neu die Partizipation an Rehamaßnahmen nicht erhöht hat. Um diese Hypothesen zu untersuchen, schätzen wir die Effekte von IP Neu auf den Bezug von Rehamaßnahmen und auf die Gesundheitsausgaben. Mit IP Neu hat der Bezug von Rehamaßnahmen stark zugenommen. Gleichzeitig nehmen die kurzfristigen Gesundheitskosten leicht zu. Eine Erklärung ist, dass AntragsstellerInnen während der Rehabilitation mehr medizinische Leistungen konsumieren. Diese Unterschiede können längerfristig verschwinden, falls AntragsstellerInnen unter IP Neu verstärkt in Beschäftigung zurückkehren. . – – The introduction of "IP New" in 2014 resulted in fundamental changes for disability pensions in Austria. The purpose of IP New was to strengthen labor market integration of individuals with health problems and to reduce sickness-related retirements. For this purpose, the temporary disability pension was abolished and instead a rehabilitation allowance was granted. At the same time, vocational and medical rehabilitation measures are carried out. This study summarizes the results of the project "Evaluation IP New". The analysis covers the period 2014-2017/2018. IP New reduced the number of temporary disability pensions by 40 percentage points in favor of an approximately equal increase in the number of rehabilitation allowance. We find that IP New had little effects on other labor market states. Although the employment situation improves slightly for individuals who are subject to the new rules, the effect is quantitatively very small. We find no effects of IP New on unemployment or sickness absence. Possible reasons for the negligible labor market effects are that many applicants are in rehabilitation and have not made any attempt to return to the labor market, or that IP Neu has not increased participation in rehabilitation measures. To investigate these hypotheses, we estimate the effects of IP New on the receipt of rehabilitation measures and on health expenditures. We find that IP New increased the probability of being assigned to a rehabilitation measure by 40 percent. At the same time, we find a slight increase in short-term health care expenditures. One explanation is that during rehabilitation applicants consume more medical services. These differences may disappear in the longer term if applicants who are subject to IP New are more likely to return to work.
Keywords: 300; Invaliditätspension (IP); Arbeitsmarktintegration; Rehabilitation; Erwerbsminderungsrente; Rentenreform; Österreich